Outpatient Total Knee Arthroplasty: A Meta-Analysis - Filippo Migliorini; Andrea Pintore; Lucio Cipollaro; Francesco Oliva; Nicola Maffulli (Applied Sciences, 2021)
Introduction: Outpatient total knee arthroplasty (TKA) is attracting growing interest. This meta-analysis compared patient reported outcome measures (PROMs), infection, readmission, revision, deep vein thrombosis (DVT), and mortality rates of outpatient versus inpatient TKA. Methods: This meta-analysis was conducted according to the 2020 PRISMA statement. In August 2021, the following databases were accessed: Pubmed, Web of Science, Google Scholar, Embase. All the clinical trials comparing outpatient versus inpatient (>2 days) TKA were considered. Studies which reported data on revision settings were not considered, nor studies which included patients discharged between one and two days. Results: Data from 159,219 TKAs were retrieved. The mean follow-up was 5.8 ± 7.6 months. The mean age was 63.7 ± 5.0 years and the mean BMI 30.3 ± 1.8 kg/m2. Comparability was found in age (p = 0.4), BMI (p = 0.3), and gender (p = 0.4). The outpatient group evidenced a greater Oxford knee score (p = 0.01). The inpatient group demonstrated a greater rate of revision (p = 0.03), mortality (p = 0.003), and DVT (p = 0.005). No difference was found in the rate of readmission (p = 0.3) and infection (p = 0.4). Conclusions: With regards to the endpoints evaluated in this meta-analysis, current evidence does not support outpatient TKA. However, given the limited data available for inclusion and the overall poor quality of the included articles, no reliable conclusion can be inferred. Further high quality clinical trials with clear eligibility criteria are required.